2019
DOI: 10.1016/j.celrep.2019.10.108
|View full text |Cite
|
Sign up to set email alerts
|

RNase H1 and H2 Are Differentially Regulated to Process RNA-DNA Hybrids

Abstract: Highlights d RNase H2 efficiently processes R-loops and rNMPs postreplicatively d rNMPs processed by RNase H2 in S phase require Rad52mediated repair d RNase H1 functions independently of the cell cycle d RNase H1 responds to R-loop-induced stress

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 39 publications
(76 reference statements)
10
101
0
2
Order By: Relevance
“…Consistently, upon fractionation of cell lysates, RNase H2 is more prominently chromatin-associated in G2/M than in S phase, but to a lesser extent in G1 (Lockhart et al, 2019), suggesting that postreplicative chromatin association of RNase H2 may be a more general feature and not just restricted to telomeres. The same work further demonstrated that G2 phase-restricted RNase H2 expression is sufficient to allow its functions both in R-loop removal and RER; while restricting expression to S phase in fact causes defects in Rloop processing as well as RER-related toxicity (Lockhart et al, 2019). It may thus be crucial to limit the peak of RNase H2 activity to a postreplicative period, possibly to minimize generation of DNA double-strand breaks arising from encounters of an oncoming replication fork with RNase H2-induced nicks during S phase.…”
Section: Rer Regulationmentioning
confidence: 68%
See 2 more Smart Citations
“…Consistently, upon fractionation of cell lysates, RNase H2 is more prominently chromatin-associated in G2/M than in S phase, but to a lesser extent in G1 (Lockhart et al, 2019), suggesting that postreplicative chromatin association of RNase H2 may be a more general feature and not just restricted to telomeres. The same work further demonstrated that G2 phase-restricted RNase H2 expression is sufficient to allow its functions both in R-loop removal and RER; while restricting expression to S phase in fact causes defects in Rloop processing as well as RER-related toxicity (Lockhart et al, 2019). It may thus be crucial to limit the peak of RNase H2 activity to a postreplicative period, possibly to minimize generation of DNA double-strand breaks arising from encounters of an oncoming replication fork with RNase H2-induced nicks during S phase.…”
Section: Rer Regulationmentioning
confidence: 68%
“…While RNase H2 did not localize to particular genomic regions in chromatin immunoprecipitations from asynchronously growing yeast cells (Zimmer & Koshland, 2016), it could be crosslinked to telomeres in cells synchronized late in S phase, at times when the bulk of genomic DNA has been replicated (Graf et al, 2017). Consistently, upon fractionation of cell lysates, RNase H2 is more prominently chromatin-associated in G2/M than in S phase, but to a lesser extent in G1 (Lockhart et al, 2019), suggesting that postreplicative chromatin association of RNase H2 may be a more general feature and not just restricted to telomeres. The same work further demonstrated that G2 phase-restricted RNase H2 expression is sufficient to allow its functions both in R-loop removal and RER; while restricting expression to S phase in fact causes defects in Rloop processing as well as RER-related toxicity (Lockhart et al, 2019).…”
Section: Rer Regulationmentioning
confidence: 84%
See 1 more Smart Citation
“…Another possibility could be that DOT1B modulates RH2 activity. Interestingly, yeast RH2 was shown to perform all its functions in the G2-phase of the cell cycle (112). It would be interesting to figure out if this is also true for trypanosomal RH2, and if DOT1B contributes via a cell cycle-dependent interaction.…”
Section: Discussionmentioning
confidence: 98%
“…Eukaryotic RNase H enzymes are classified into two main types, RNase H1 and RNase H2, that are differentially regulated during the cell cycle and differ in the range of substrates they act on. [ 61 ] Both types can resolve DNA:RNA hybrids in R‐loops and, in addition, RNase H2 plays a specialized function in the cleavage of single ribonucleotides embedded in the genome. [ 62 ] RNase H enzymes have been directly linked to the degradation of DNA:RNA hybrids formed at DSBs and several observations support their functional contribution to DNA repair.…”
Section: Resolution Of Dna:rna Hybrids At Dsbsmentioning
confidence: 99%